Design and implementation of clutch-by-wire system for automated manual transmissions. (27th September 2004) - Moon, S.E.; Kim, M.S.; Yeo, H.; Kim, H.S.; Hwang, S.H.; Song, H.L.; Han, K.S.
With the growing traffic density and increasing comfort requirements, the automation of the drive train will gain importance in vehicles. The automatic clutch actuation relieves the drivers especially in urban driving and stop-and-go traffic conditions. This paper describes the dynamic modelling of a clutch actuator and clutch spring. The dynamic model of the clutch system is developed using MATLAB/Simulink, and evaluated by experimental data using a test rig. This performance simulator is useful to develop the clutch-by-wire (CBW) system for an automated manual transmission (AMT). The electromechanical type CBW system is also implemented as an automatic clutch for AMT. The prototype of the CBW system is designed and implemented systematically, and composed of an electric motor, worm gear and crank mechanism. The test rig is developed to perform the basic function test of the automatic clutch, and the developed prototype is validated by the experimental data employing the test rig.